2019
DOI: 10.9734/ijtdh/2019/v36i430149
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pulmonary Tuberculosis among Presumptive Cases in Rivers State, Nigeria

Abstract: Background: Tuberculosis (TB) is a leading cause of death in children but it is underdiagnosed and underreported in children. Objective: To determine the prevalence of pulmonary TB in children among presumptive cases of TB and to compare the diagnostic efficacy of different screening tool for TB in children.  Materials and Methods: This study was a descriptive prospective study carried out over one year in nine general health facilities that can provide diagnosis and treatment for tuberculosis in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Chronic cough was found in 75% of this study and in all patients with Pulmonary TB and this is similar to findings in other studies in children with pulmonary TB [15][16][17]. This cough is initially unproductive but with progressive inflammation and tissue necrosis becomes wet and productive of sputum.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Chronic cough was found in 75% of this study and in all patients with Pulmonary TB and this is similar to findings in other studies in children with pulmonary TB [15][16][17]. This cough is initially unproductive but with progressive inflammation and tissue necrosis becomes wet and productive of sputum.…”
Section: Discussionsupporting
confidence: 90%
“…Individuals from low social class tend to reside in densely populated areas where human traffic and contact is high and this increases TB transmission. However, TB is sometimes also found in person from high social class, so a high index of suspicion is required in all patients presenting with features in keeping with presumptive diagnosis of TB [15].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that all the social class was represented but more (46.1%) of them belonged to the lower social class. This is typical of findings in other studies as tuberculosis has been described as a disease of poverty [18,22]. These individuals are more likely to live in overcrowded homes and in areas with high population density.…”
Section: Discussionsupporting
confidence: 85%
“…It was found that over half (58.7%) of the recruited TB contacts were males while 50.8% were children of the TB cases. Though these children were recruited by contact tracing, it is not surprising to find that many studies have shown more males than females as having tuberculosis [18][19][20][21]. That more of the recruited child contacts are children of TB cases emphasizes the need for active contact tracing once an adult case of TB is diagnosed as childhood TB is a reflection of adult TB pool.…”
Section: Discussionmentioning
confidence: 99%